PENGEMBANGAN MEDIA POP-UP BOOK PETUALANGAN LOKUS UNTUK MENINGKATKAN KEMANDIRIAN BELAJAR SISWA - Ningrum, Alia Putriana; Lestari, Bella Pramudya; Laili, Iftitah Nur; Nugraheni, Qulya Alvin Jana (Fakultas Ilmu Pendidikan Universitas Muhammadiyah Jakarta, 2025)
The study aims to develop three-dimensional Pop-Up Book learning media to enhance students' learning independence on the topic of cubes and rectangular prisms at SDN Merjosari 2, Malang City. The method applied is Research and Development (RnD) using the 4D model (Define, Design, Develop, Disseminate). The research subjects are sixth-grade students, with research instruments in the form of questionnaires. Validation results show that the Pop-Up Book media is considered valid based on expert validation, with scores of 97.3% (media experts) and 89.2% (content experts). The use of this media has proven to significantly improve learning independence. The average learning independence score increased from 72.56 before the intervention to 93.11 after the intervention, with an N-gain of 0.7405, categorized as high. Additionally, the Pop-Up Book was rated as very appealing, with a score of 98%. Therefore, the Pop-Up Book is proven to be highly engaging and effective in enhancing students' learning independence.